2024
DOI: 10.3390/jmse12030434
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Wake Evolution under Vertical Staggered Arrangement of Wind Turbines of Different Sizes

Lidong Zhang,
Zhengcong Feng,
Yuze Zhao
et al.

Abstract: During the expansion of a wind farm, the strategic placement of wind turbines can significantly improve wind energy utilization. This study investigates the evolution of wake turbulence in a wind farm after introducing smaller wind turbines within the gaps between larger ones, focusing on aspects such as wind speed, turbulence intensity, and turbulence integral length scale. The flow field conditions are described using parameters like turbulence critical length and power spectral density, as determined throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Xu et al [25] found that by improving the Caputo-Fabrizio fractional order derivative SR in the vibration diagnosis of wind turbine systems, the weak vibration signals are amplified, which effectively improves the vibration detection efficiency of wind turbines operating in strong turbulence environments. Zhang et al [26] proposed a new layout method for wind turbines. They studied the evolution process of wind turbine wake through the wind tunnel test, and analyzed the speed distribution and turbulence characteristics of wind farms through the turbulence intensity and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [25] found that by improving the Caputo-Fabrizio fractional order derivative SR in the vibration diagnosis of wind turbine systems, the weak vibration signals are amplified, which effectively improves the vibration detection efficiency of wind turbines operating in strong turbulence environments. Zhang et al [26] proposed a new layout method for wind turbines. They studied the evolution process of wind turbine wake through the wind tunnel test, and analyzed the speed distribution and turbulence characteristics of wind farms through the turbulence intensity and other factors.…”
Section: Introductionmentioning
confidence: 99%